The Tsunami Simulation Generated by ‘Anak Krakatau’ Volcano Flank Collapse using MIKE 21Hydrodynamics Flexible Mesh with Manning Number Variation - Hanah Khoirunnisa; Wahyu Hendriyono; Mardi Wibowo (Politeknik Negeri Batam, 2021)
This study aims to calculate the tsunami investment and the estimated arrival time at several locations around the Sunda strait, caused by the December 2018 Krakatao's eruption. The propagation of the tsunami wave is simulated using MIKE 21 Hydrodynamics Flexible Mesh (HD FM). The spatial data consist of the bathymetry and topography of the Sunda Strait area and its surroundings, whilst assumptions are made on the tsunami source topology and its exact location. Several runs of the simulation are then conducted by varying the Manning Number, i.e. bed resistance values, at the tsunami source and throughout the simulation domain, which accordingly would influence the propagation speed, inundation, and arrival time. Smaller Manning's values, which correspond to increasing roughness, are applied at locations closer to the tsunami source. In this simulation, Manning's number ranges from 10 to 40 m1/3s-1. Surface elevation, still water depth, and u and v velocity components are generated from this simulation.